Adult weight change and risk of colorectal cancer in the European Prospective Investigation into Cancer and Nutrition - Aleksandrova, K; Pischon, T; Buijsse, B; May, A; Peeters, P; Bueno-De-Mesquita, H; Jenab, M; Fedirko, V; Dahm, C; Siersema, P; Freisling, H; Ferrari, P; et al. (2013)
Aim Weight change during adult life may reflect metabolic changes and influence colorectal cancer (CRC) development, but such role is not well established. We aimed to explore the association between adult weight change (from age 20 to 50) and CRC risk. In particular, we investigated differences according to colon and rectal cancer, sex and measures of attained adiposity. Methods We included 201,696 participants from six participating countries in the European Prospective Investigation into Cancer and Nutrition (1992-2010). During a mean follow-up of 11.2 years 2384 (1194 in men and 1190 in women) incident CRC cases occurred. Cox proportional hazard models adjusted for body mass index at age 20 and lifestyle factors at study recruitment were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results After multivariable adjustment, each kg of weight gained annually from age 20 to 50 was associated with a 60% higher risk of colon cancer (95% CI 1.20-2.09), but not rectal cancer (HR 1.13, 95% CI 0.79-1.62, Pinteraction = 0.04). The higher risk of colon cancer was restricted to people with high attained waist circumference at age 50 (HR 1.82, 95% CI 1.14-2.91, P interaction = 0.02). Results were not different in men and women (Pinteraction = 0.81). Conclusion(s) Adult weight gain, as reflected by attained abdominal obesity at age 50, increases colon cancer risk in both men and women. These data underline the importance of weight management and metabolic health maintenance in early adult life years for colon cancer prevention. © 2013 Elsevier Ltd. All rights reserved.